Gene Promoter-Methylation Signature as Biomarker to Predict Cisplatin-Radiotherapy Sensitivity in Locally Advanced Cervical Cancer - Contreras-Romero, Carlos; Pérez-Yépez, Eloy-Andrés; Martinez-Gutierrez, Antonio Daniel; Campos-Parra, Alma; Zentella-Dehesa, Alejandro; Jacobo-Herrera, Nadia; López-Camarillo, César; Corredor-Alonso, Guillermo; Martínez-Coronel, Jaime; Rodríguez-Dorantes, Mauricio; de León, David Cantu; Pérez-Plasencia, Carlos (Frontiers in Oncology, 2022)
Despite efforts to promote health policies focused on screening and early detection, cervical cancer continues to be one of the leading causes of mortality in women; in 2020, estimated 30,000 deaths in Latin America were reported for this type of tumor. While the therapies used to treat cervical cancer have excellent results in tumors identified in early stages, those women who are diagnosed in locally advanced and advanced stages show survival rates at 5 years of <50%. Molecular patterns associated with clinical response have been studied in patients who present resistance to treatment; none of them have reached clinical practice. It is therefore necessary to continue analyzing molecular patterns that allow us to identify patients at risk of developing resistance to conventional therapy. In this study, we analyzed the global methylation profile of 22 patients diagnosed with locally advanced cervical cancer and validated the genomic results in an independent cohort of 70 patients. We showed that BRD9 promoter region methylation and CTU1 demethylation were associated with a higher overall survival (p = 0.06) and progression-free survival (p = 0.0001), whereas DOCK8 demethylation was associated with therapy-resistant patients and a lower overall survival and progression-free survival (p = 0.025 and p = 0.0001, respectively). Our results suggest that methylation of promoter regions in specific genes may provide molecular markers associated with response to treatment in cancer; further investigation is needed.